Editorial Freedom in Academic Publishing: On the First Decade of the Open Library of Humanities. - Harris-Birtill, Rose (Open Library of Humanities, 2025)
This editorial commemorates the tenth anniversary of diamond open access journal publisher the Open Library of Humanities (OLH) and its flagship journal, the Open Library of Humanities journal (OLHJ). Launched in 2015, the OLH serves as an innovative model for sustainable and equitably-funded scholarly publishing that now supports over 30 peer-reviewed humanities and social sciences journals. Discussing the OLHJ's rolling publication format as a key factor in its success, this article draws on the experiences of academic editors to emphasise the importance of retaining editorial agency throughout the journal publication process. Recognising increasing corporate pressure on editors to compromise their academic integrity in favour of increasing profits, the article reveals the growing trend of mass resignations of journal editors in recent years, highlighting the fundamental importance of editors' ethical decisions in extending the global scholarly ecosystem for the common good. Building on the 2002 Budapest Open Access Initiative (BOAI) and its 20th anniversary recommendations, this article calls for a renewed commitment to its open access principles, urging the academic community to 'think globally, act locally'. Applying Jonathan Lear's concept of 'radical hope' as a powerful catalyst for the open access movement, the editorial frames collective action as a vital response to global crises in academic communities. It details vital practical steps that researchers, editors and educators can take to help advance the BOAI's goals, concluding that such individual ethical choices and collective actions are crucial for the future of the open access movement.